"Streptomyces massilialgeriensis" sp. nov., a new bacterial species isolated from an extremely saline soil collected from the dry lake of Ank el Djamel in Algeria. (January 2018) - Djaballah, C.E.; Kitouni, M.; Raoult, D.; Khelaifia, S.
Abstract: We report here the main characteristics of " Streptomyces massilialgeriensis " strain S35 T (CSUR = P3927), a new bacterial species within the Streptomyces genus, isolated from an extremely saline soil sample collected from the site of Garaet Ank Djemel in the Wilaya of Oum El Bouaghi, Algeria.